The Perceptions of Communication Science Students at IISIP YAPIS Biak Papua on the Implementation of MBKM (Merdeka Belajar Kampus Merdeka) Program - Jelita Purnamasari; Rahmah Agustiani (Momentum Matrix: International Journal of Communication, Tourism, and Social Economic Trends, 2024)
The purpose of the research was to know about the perceptions of the Communication Science students of IISIP YAPIS Biak Papua, on the implementation of MBKM program. The method used of the research was descriptive qualitative. The informants consisted of 2 which is the students from semester 5 that had participated the exchange program, which is L is from Batch 2 and R from Batch 3. The data collected by using interview. The data analyzed by using the theory of Miles and Huberman. The result of the research show that, the students perceived the MBKM program especially the students exchange program (1) has impacted their academic growth and1) has impacted their academic growth and give networking opportunities, (2) has the area for improving which is about the late of funding disbursement process, and (3) need to be recommended to other students in order to broaden their perspectives and networking.